Weibull parameters evaluation by different methods for windmills farms. (February 2020) - Shaban, Auday H.; Resen, Ali K.; Bassil, Nathalie
Abstract: Electrical power generated from the wind's motion is one of the most common clean and renewable energy produced. The wind turbines used to convert wind mechanical power to electricity have to be placed at a site presenting favorable conditions. This work focuses on finding an accurate method for modeling the power generated by a wind farm using Weibull distribution. Experimental data collected at AL-Najaf site – Iraq – is used to determine the best theoretical method to hold in order to determine the Weibull parameters. The data was collected on different levels above the ground 10, 30, and 50 m. Four criteria were displayed to assess the wind data fitting procedures; these are Root Mean Square Error, Chi-Square, correlation coefficient, and coefficient of determination. The valid distribution model was determined according to specific conditions that gives the best results. The findings indicate that the Equivalent Energy Method is the best to calculate the value of the Weibull shape parameter and the Weibull scale parameter for the Weibull distribution curves at this site based on the goodness of fit tests.